Effects of Herbal Tea Residue on Growth Performance, Meat Quality, Muscle Metabolome, and Rumen Microbiota Characteristics in Finishing Steers - Li, Ling; Sun, Xiaohong; Luo, Junyi; Chen, Ting; Xi, Qianyun; Zhang, Yongliang; Sun, Jiajie (Frontiers in Microbiology, 2022)
Herbal tea residue (HTR) contains various medicinal and nutritional components and is a potential high-quality unconventional source of roughage. In this study, a total of 30 healthy Simmental crossbred finishing steers were equally divided into two groups: CN (fed with a basic diet) and RE (HTR replaced Pennisetum purpureum). HTR did not alter the growth performance of steers but increased the net meat rate, tenderness, and water-holding capacity and increased the moisture content and oleic acid and linoleic acid concentrations in longissimus dorsi. It altered muscle metabolic pathways and improved rumen fermentation by increasing the propionic acid concentration and propionic acid-to-acetic acid ratio. We studied the steers’ rumen microbial community composition and determined their correlation with the tested parameters. Certain rumen microorganisms were closely associated with muscle glucolipid metabolites and rumen NH3-N and volatile fatty acid levels. Our findings suggest that, as a functional roughage source, HTR improved the meat quality to a certain extent of steers by altering the rumen microbial composition and affecting the rumen fatty acid composition and muscle glucolipid metabolism.